2012
DOI: 10.4314/wsa.v38i3.6
|View full text |Cite
|
Sign up to set email alerts
|

A groundwater-planning toolkit for the main Karoo basin: Identifying and quantifying groundwater-development options incorporating the concept of wellfield yields and aquifer firm yields

Abstract: This paper provides an overview of groundwater-planning tools that were developed during a Water Research Commission project that was initiated due to the need to place the significant knowledge on groundwater of the Karoo Basin within the realms of water resource planning. In essence, the project aimed to identify favourable areas of groundwater potential for bulk municipal water supplies, to provide a method to quantify them, and to package the information so that it is assessable for planning purposes. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 3 publications
2
20
0
Order By: Relevance
“…6a). Similar results have been reported for the Eastern Cape Karoo (Department of Water Affairs and Forestry 2010; Murray et al 2012;SRK Consulting 2012). However, this research has also identified increased areas where water exhibits a considerably lower quality (poor to unacceptable).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…6a). Similar results have been reported for the Eastern Cape Karoo (Department of Water Affairs and Forestry 2010; Murray et al 2012;SRK Consulting 2012). However, this research has also identified increased areas where water exhibits a considerably lower quality (poor to unacceptable).…”
Section: Resultssupporting
confidence: 77%
“…Similar groundwater depths have been observed for the Eastern Cape Karoo (Department of Water Affairs and Forestry 2010; Murray et al 2012;SRK Consulting 2012).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations